Minas do RAP e Breakdance em Manaus: da zona de conforto para a zona de confronto - Souza, Talita Menezes de (2020)
This research is due to concerns about why the small participation of women involved in Hip Hop in the city of Manaus. Due to the lack of academic studies about women in Hip Hop, there was an impulse to conduct a research that problematizes this situation. This study has as main objective to understand their participation and perceptions in the Hip Hop movement in Manaus. Here we will present Hip Hop as an active element and as a scream for the legitimation of communities and the people who live in them, and in this context, we will address the importance of women in this movement, as well as their lived experiences in it. This research has an entirely qualitative approach, thus, the methodology used for data collection was made through interviews with five of the currently leading women in Hip Hop in Manaus, in order to hear about their experiences. In general, the research realizes that collectives and events aimed specifically for women are important strategies for strengthening their gender inside this movement, and that, the political awareness among participants who practice Rap is developed with greater intensity than in those participating in Breakdance. To conduct these discussions, we used authors such as Zygmunt Bauman, Stuart Hall, Judith Butler, Michele Perrot, Sérgio Leal and Andréia Moasab, as well as other theorists.